The strictures of inheritance : the Dutch economy in the nineteenth century - Zanden, J. L. van (Princeton economic history of the Western world., 2004)
"A major feat of research and synthesis, this book presents the first comprehensive history of the Dutch economy in the nineteenth century - an important but poorly understood piece of European economic history. Based on a detailed reconstruction of extensive economic data, the authors account for demise of the Dutch economy's golden age. After showing how institutional factors combined to make the Dutch economy a victim of its own success, the book traces its subsequent emergence as a modern industrial economy."--Jacket